2007
DOI: 10.1111/j.1469-7998.2006.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Can pipistrelles, Pipistrellus pipistrellus (Schreber, 1774) and Pipistrellus pygmaeus (Leach, 1825), foraging in a group, change parameters of their signals?

Abstract: KeywordsPipistrellus pipistrellus; P. pygmaeus; echolocation in the field and laboratory; monospecific and mixed-species groups. Correspondence AbstractEcholocation behaviour and the structure of calls of Pipistrellus pygmaeus and Pipistrellus pipistrellus were studied by using a time expansion bat detector. Echolocation signals were recorded in the field in south-eastern Moravia and northern Bohemia (Czech Republic) and in an ad hoc experimental laboratory. For each of the species, multivariate analysis of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 42 publications
0
22
1
Order By: Relevance
“…Two pipistrelle bats, Pipistrellus pipistrellus and Pipistrellus pygmaeus, produce calls with peak frequencies of 45 and 55 kHz, respectively. Their call design changed when they flew with conspecifics but their calls remained the same when flying with heterospecifics (Bartonicka et al, 2007). The authors of this previous study suggested that call difference between these two pipistrelle species, which is 10 kHz, C. Chiu, W. Xian and C. F. Moss is enough to avoid jamming among heterospecifics.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Two pipistrelle bats, Pipistrellus pipistrellus and Pipistrellus pygmaeus, produce calls with peak frequencies of 45 and 55 kHz, respectively. Their call design changed when they flew with conspecifics but their calls remained the same when flying with heterospecifics (Bartonicka et al, 2007). The authors of this previous study suggested that call difference between these two pipistrelle species, which is 10 kHz, C. Chiu, W. Xian and C. F. Moss is enough to avoid jamming among heterospecifics.…”
Section: Discussionmentioning
confidence: 98%
“…Call design separation was affected by the spatial distance between paired bats and baseline similarity in call design, which further suggests that the bat actively adjusts its call design to avoid signal interference from conspecifics. Several bat species, including R. hardwickei, Balantiopteryx plicata, T. brasiliensis and Tadarida teniotis, have been reported to adjust their call frequencies when flying in groups (Bartonicka et al, 2007;Habersetzer, 1981;Ibánez et al, 2004;Ratcliffe et al, 2004;Ulanovsky et al, 2004). Some bat species modified temporal features rather than spectral features of their vocalizations to avoid call interference from conspecifics (Obrist, 1995).…”
Section: Global Signal Adjustments In the Presence Of Conspecificsmentioning
confidence: 99%
“…When foraging with conspecifics in the field, some frequencymodulated (FM) bat species have been observed to shift the terminal frequency portion of the downward FM sweep of the fundamental component (terminal frequency; TF) of their own pulse to maintain frequency separation between individuals, suggesting that the bats perform the JAR by shifting frequency ranges during group flight (Bartonička et al, 2007;Chiu et al, 2009;Ibánez et al, 2004;Miller and Degn, 1981;Necknig and Zahn, 2011;Surlykke and Moss, 2000;Ulanovsky et al, 2004). JAR behavior has also been observed by generating acoustic stimuli through an ultrasonic speaker.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to European pipistrelle bats (Schnitzler et al 1987, Kalko and Schnitzler 1993, Kalko 1994, Bartonièka et al 2007, P. abramus mostly emits long duration QCF pulses, while searching for prey. The structure of echolocation signals reflects the foraging ecology of many bats Kalko 1998, Jones 1999).…”
Section: Modulation Of Echolocation Pulsesmentioning
confidence: 99%
“…Previous studies show that European pipistrelle bats flexibly adjust their echolocation pulses in relation to acoustic characteristics (eg the proximity of echo clutter) associated with different foraging habitats (Swift 1980, Racey and Swift 1985, Kalko and Schnitzler 1993, Bartonièka and Øehák 2005, Bartonièka et al 2007. Field studies also indicate that some bat species are highly flexible in signal structure while searching for prey [eg Nyctalus noctula (Zbinden 1989, Rachwald 1992, M. dasycneme (Britton et al 1997)].…”
mentioning
confidence: 99%